Characterization and Commissioning of a Triple-GEM Detector (2023)
We present in detail the characterization and commissioning of a triple Gas Electron Multiplier (triple-GEM)detector. The response to various sources of radiation was studied, and its efficiency, gain, energy resolution,and temporal resolution were calculated. We found an energy resolution of 19.5%, a temporal resolution of40 ns., and a maximum gain of 5×106. We conclude that the detector can be confidently used in furtherstudies of medical dosimetry, since it is working in the proportional mode.